The Impact of Leadership Style and Work Motivation on Nurse Performance - Sultan Sultan; Joko Prasetyo (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to examine and analyze the effect of leadership style and motivation on the performance of nurses at the Jayapura Papua Regional General Hospital. The population in this study were all nurses at the Jayapura Regional General Hospital in Papua, totaling 348. The technique used to determine the sample in this study was simple random sampling technique to measure the sample size to be studied. After doing calculations with the slovin formula, the number of samples used after being rounded up is 100 nurses. The data source for this research is primary data, namely data obtained from the results of distributing questionnaires to all respondents. The statistical method used to test the hypothesis is multiple linear regression analysis. This research also uses validity and reliability tests, t-test (partial), f-test (simultaneous) correlation coefficient test (r), coefficient of determination (r2). From the results of hypothesis testing it has been proven that competence and motivation have a significant influence on the performance of nurses at the Jayapura Papua Regional General Hospital.